From Insecurity to Confidence: Exploring Moral Values in “Tall Girl” Movie by Nzingha Stewart - Dian Agatha, Shahnaz; Deni Ariyaningsih, Nyoman (Riviera Publishing, 2024)
This study examines the moral values presented in the